INFLUENCE OF VITREOMACULAR INTERFACE ON ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY USING TREAT AND EXTEND TREATMENT PROTOCOL FOR AGE-RELATED MACULAR DEGENERATION (VINTREX). Issue 9 (September 2015) - Houston, Samuel K.; Rayess, Nadim; Cohen, Michael N.; Ho, Allen C.; Regillo, Carl D.
Abstract : Purpose: To determine the influence of vitreomacular adhesion (VMA) on treatment outcomes in patients with neovascular age-related macular degeneration who were treated with anti-vascular endothelial growth factor agents using a treat and extend treatment regimen. Methods: A retrospective consecutive case series of 204 eyes from 181 patients with a minimum of 1 year of follow-up at Wills Eye Hospital Retina Service. Vitreomacular interface characteristics were determined by spectral domain optical coherence tomography. One hundred and fifty-three eyes (75%) had no signs of VMA (non-VMA), and 51 (25%) had VMA. Results: Baseline mean visual acuity was 20/133 with a mean central retinal thickness of 350.5 μ m in the non-VMA group and was 20/145 with 371.8 μ m in the VMA group. Mean visual acuity in the non-VMA group was 20/83 and 20/64 at Years 1 and 2, respectively ( P < 0.01 to baseline). Mean visual acuity in the VMA group was 20/81 and 20/85 at Years 1 and 2, respectively ( P < 0.01 to baseline). The central retinal thickness was 289.71 μ m and 267 μ m at Years 1 and 2, respectively ( P < 0.01 to baseline) in the non-VMA group and was 305.3 μ m and 289.24 μ m ( P < 0.01 to baseline) in the VMA group. The mean total number of injections at Year 1 for non-VMA was 7.4 compared with 8.4 in VMA ( P = 0.001) and 5.5 versus 6.7 for the 2 groups in Year 2 ( P = 0.027). The mean longest extension at Year 1 was 11.8 weeks compared with 10.1 week ( P = 0.005) and for Year 2 was 14.1 weeks compared with 12 weeks ( P = 0.041). Conclusion: The vitreomacular interface seems to have a significant influence on anti-vascular endothelial growth factor treatment intervals but not visual acuity or exudative control outcomes. Eyes with VMA on spectral domain optical coherence tomography at baseline may require more intensive treatment with decreased ability to extend treatment intervals. Abstract : The vitreomacular interface may have a significant effect on treatment outcomes of neovascular age-related macular degeneration using a treat and extend protocol. Patients with vitreomacular adhesion may need more intensive treatment and have less of an ability to extend treatment intervals. As a result, anatomical factors may contribute to individual treatment responses and should be evaluated and considered in treatment decisions for neovascular age-related macular degeneration.